Baseline anemia and its associated factors among adult cancer patients at Northwest Amhara Regional State Referral Hospitals, Northwest Ethiopia, 2021 - Wassie, Yilkal Abebaw; Zegeye, Alebachew Ferede; Gebrehana, Deresse Abebe; Tsega, Sintayehu Simie; Kibralew, Getasew; Fentahun, Setegn; Setegn, Abebaw; Nakie, Girum (Frontiers in Oncology, 2024)
Introduction Currently, the problem of cancer has been increasing around the world, predominantly in middle- and low-income countries. Anemia, a major and often overwhelming health burden for cancer patients, significantly distorts their quality of life. It is well-established that the length of treatment increases the frequency of anemia, with hematological malignancies experiencing nearly double the rate compared to solid tumors. Despite this established knowledge, data on the prevalence of anemia among cancer patients in Ethiopia remains scarce, according to the investigators. Objective This study aimed to assess the prevalence of baseline anemia and associated factors among adult cancer patients at Northwest Amhara Comprehensive Specialized Hospitals, oncology treatment units, Northwest Ethiopia, in 2021. Methods This study employed an institutional-based cross-sectional design and was conducted in Northwest Amhara Comprehensive Specialized Hospitals. A systematic random sampling technique was used to select 315 participants. The data were collected using interviewer-administered questionnaires and chart reviews of existing medical records using a structured and pretested questionnaire format. The data were entered into Epi. Data version 4.6 and analyzed using Stata version 14.0. Bivariable and multivariable logistic regression were carried out to identify factors associated with anemia. Adjusted odds ratios with a 95% confidence interval and variables with a p-value of < 0.05 were considered significantly associated with anemia. Results The prevalence of baseline anemia among adult patients with cancer was found to be 34.84%. Being a woman (AOR = 1.97; 95% CI: 1.00–3.87), being underweight (AOR = 1.96; 95% CI: 1.09–3.52), and having stage III cancer (AOR = 2.35; 95% CI: 1.12–3.01) were significantly associated with anemia. Conclusion The prevalence of baseline anemia among adult cancer patients was significant. Women, cancer patients with an underweight body mass index, and those diagnosed with clinical-stage III cancer were more likely to have baseline anemia. For health policymakers and healthcare providers, it is better to give special attention to female patients, patients who are underweight, and patients with advanced-stage cancer to reduce the risk of developing the outcome. This would allow for timely intervention to manage anemia and potentially improve treatment tolerance and quality of life for cancer patients.